Income status of the ultra poor - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This paper reports on income status, major sources of income and determinants of income of the ultra poor Mean per capita income was calculated to be Tk.3,385, per annum that was even less than the estimated lower poverty line income. The contribution of males and females to total household income was found to be 66% and 34% respectively. Variations in the male female contributions were due to differences in the number of economically active males and females within the household, household resource base, and sex and occupation of the household heads. The study came up with the following conclusions. First of all differential income and its sources for different region indicate that the effect of any similar kind of intervention would be different for different regions. To minimize regional variations detail knowledge on specific region would help for its further modification. Secondly, insignificant positive contribution of external capital and NGO presence indicate that micro-credit can not be the only alternative for their poverty eradication. Since 77% of the ultra poor were mainly depended on wage employment, any wage-based development would be more beneficial to them. Thirdly, high dependence on others' help indicated that in any development programme for to the ultra poor, a provision of safety net would be necessary.